Campos de formación del currículo del ingeniero agropecuario - Fierro Jaramillo, Natacha Del Cisne (2018)
The objective of this work was to determine the priority training fields for those who chose as a professional career in Agricultural Engineering. This study was conducted between 2014-2015 in Ecuador, 7 - South Planning Zone. Different participatory tools were used as a measurement instrument, including techniques such as questionnaires, interviews and discussion groups, which were designed with questions aimed at obtaining precise answers. The results allowed to know which were the fields of training in the profile of the future agricultural professional. The results indicate that the actors involved in the agricultural field prefer that the student has more training in Praxis Profesional (professional practices), since it is a practical career. Besides, they consider important training in the field of Knowledge Integration and Context and Culture. The results of this work were contributed to the restructuring of the career the Agricultural engineering of the Universidad Técnica Particular de Loja, which has been approved by the Consejo de Educación Superior (CES) in 2016.